The Use of the Form: Functional Analysis of Lower Component Artifacts from Piedra Museo (Santa Cruz, Argentina) - Lynch, Virginia (2012)
The Piedra Museo archaeological site is located in the central plateau of Santa Cruz, Argentina. This site includes two rock shelters named ‘Alero El Puesto 1’(AEP-1) and ‘Alero El Galpón 2’ (AEG-2) site, both sites located on the basis of a tuffaceous conglomerate of Jurassic marine ingression called El Museo Formation. The lower component of AEP-1 has been considered as a killing prey and primary meat cutting area in the Pleistocene-Holocene. Although many macroscopic analyses of lithic artifacts have been carried out on this area, little is known about the used of these artifacts. The main objective of this study is to provide preliminary results of use-wear analysis addresses to determine the functionality of archaeological artifacts and to assess the relationship between artifacts functionality and the pieces design. We included microscopic analysis of lithic artifacts from stratigraphic units 4/5 and 6, characterized by the presence of unifacial pieces, flakes and fragments of fishtail proyectil points. Results showed that most of the piece edges were altered by post-depositional processes that hindered our capacity of identifying use-wear traces. Despite these problems, the application of use-wear method allowed us to establish general guidelines about the consumption strategies of hunting-gatherers societies.